Optimalisasi Manajemen Kelas dalam Meningkatkan Efektivitas Pembelajaran Bahasa Arab di Madrasah Ibtidaiyah - Isnol Khotimah; Arini Hidayati (KURAS Institute, 2026)
This study is motivated by students’ low ability to read Arabic texts and the less conducive classroom conditions in Arabic language learning at MIN 1 Probolinggo. These issues highlight the importance of effective classroom management strategies in supporting the learning process. This study aims to analyze the classroom management strategies implemented by teachers in Arabic language learning. This research employs a qualitative approach with a descriptive design. Data were collected through interviews, observations, and documentation involving Arabic language teachers and students. The findings reveal that teachers implement six main classroom management strategies: planning, organizing, directing, conditioning, supervising, and evaluating. These strategies are applied through structured lesson preparation, interactive learning methods such as language games, classroom arrangement, and continuous monitoring of student activities. The study also identifies supporting factors, including teacher readiness and student engagement, as well as inhibiting factors such as differences in student abilities, limited time, and inadequate facilities. This study implies that effective classroom management significantly contributes to creating a conducive, interactive, and engaging learning environment, thereby enhancing students’ participation and understanding in Arabic language learning.